(untitled) (Research, Society and Development, 2025)
This study aimed to investigate the influence of material, human resource and physical structure management on the efficiency of procedures performed in surgical centers, focusing on the strategic role of the nurse manager. Through a bibliographical research, aspects related to the organization of supplies, team coordination, application of protocols and integrated management of surgical processes were analyzed. The results showed that active leadership by the nurse contributes significantly to the reduction of operational failures, optimization of operating room turnover and increased patient safety. In addition, systematic control of resources and evidence-based management performance strengthen the quality of care and promote greater institutional efficiency. It is concluded that the nurse manager plays an essential role in the articulation between team, structure and protocols, being a key player for a functional, productive and safe surgical center.